Upaya Unit Dikyasa Sat Lantas Polres Bogor Dalam Mengurangi Kemacetan Di Jalur Puncak - Nabil, Muhammad (Indonesian Journal of Police Studies, 2020)
This research is motivated because of the high number of congestion in the Peak route. Congestion occurs because on the Peak there are many tourist attractions, the amount of population growth in Bogor Regency, and the number of narrowing on the road. In connection with the main tasks of the Traffic Unit, efforts are needed to deal with congestion by the Bogor Traffic Police Unit, especially the Dikyasa Unit through traffic management and engineering. Based on this background, a study was carried out with the aim of finding out how the efforts of the Unit of the Bogor Sat Traffic Police Unit in Reducing Congestion in the Peak Lane. This research methodology uses a qualitative approach with a focus of research on the efforts of Dikaysa units in reducing congestion. Furthermore, to obtain data, researchers used primary data sources obtained through interviews and observations as well as secondary sources obtained through document review. Then the research results were analyzed with Management Theory and Role Theory then the concept of Traffic and Traffic Engineering Concepts. Based on the results of the study, it was found that the situation and condition of the traffic flow in the Puncak lane still experience traffic jams at certain times such as during holidays such as Saturday week, red date, and national holiday. But on ordinary days congestion can be overcome. The effort to deal with congestion is by placing members of the Bogor Traffic Police Unit to carry out arrangements and conduct traffic management and engineering using a one-way system, as well as carrying out lighting and coordination with related agencies. So from the findings when carrying out research, it is suggested to the Bogor Police Traffic Unit Unit Satyas Sat, to increase the number of personnel so that performance is more optimal, coordinate with related agencies more intensively, and make a creative effort by utilizing the Zenly Application namely the Peak Alternative Pathway program.